An examination of the role of inverted dark tetrad items on structural properties and construct validity - Blötner, Christian; Grüning, David (European journal of psychological assessment, 2023)
The use of inverted items is under vigorous debate in psychometric research. However, especially in the field of the Dark Tetrad - a compound of the aversive yet subclinical traits Machiavellianism, narcissism, psychopathy, and sadism -, the use of items in which high endorsement indicates low levels appears promising to obtain more information about low scores on the four traits. In this preregistered research (N = 500), we developed an alternative version of the Short Dark Tetrad (SD4) which - unlike the original SD4 - has a balanced set of regular and inverted items. Following the theory of utilizing inverted items, we demonstrate that more information (in the sense of item response theory) can be obtained from the newly devised Mixed SD4 (MSD4) as compared to the original SD4. Thereby, the scores of the MSD4 can be validly interpreted in the sense of the underlying traits' theories (i.e., construct validity), and the SD4 and the MSD4 yield highly similar nomological networks. We conclude that including inverted items is advantageous for the assessment of the Dark Tetrad. More generally, we present this case as a demonstration that balanced item sets are necessary to capture traits and behaviors exhaustively.
Gesehen am 25.07.2024